Application of oral nutritional supplements to control body weight loss in postoperative patients suffering from solid tumors: a systematic review and meta-analysis - Liu, Ying; Wu, Zhen; Shao, Tingting; Zheng, Wanzhen; Huang, Jing (Frontiers in Nutrition, 2025)
ObjectiveThis study aims to summarize the impact of oral nutritional supplements (ONSs) on mitigating body weight loss (BWL) in patients following surgical treatment for solid tumors.MethodsA systematic and comprehensive search of four major publicly available databases was conducted up to May 2024 to identify studies for inclusion in the analysis. Data from eligible studies were extracted, and pooled mean differences (MD) along with their 95% confidence intervals (CIs) for BWL were computed.ResultsA total of 12 randomized controlled trials (RCTs) with 2,268 participants were finally included. The group receiving oral nutritional supplements demonstrated a statistically significant reduction in weight loss compared to the control group, with a mean difference of 1.11 (95% CI: 0.52–1.70), an I2 statistic of 97.0%, and a p-value less than 0.01.ConclusionThe meta-analysis provide evidence that ONSs effectively reduce BWL in postoperative patients with solid tumors. Additionally, ONS with lower daily caloric intake demonstrated superior efficacy in reducing BWL.